WAWANCARA PSIKOLOGI SEBAGAI ALAT UNTUK MEMAHAMI IDENTITAS, PENCAPAIAN, EMOSIONAL REMAJA - Oktaviani Simbolon; Rizki Aprilia Lumbantobing; Ingot Harminto Situmorang; Dorlan Naibaho (Jurnal Ilmiah Multidisiplin Ilmu, 2024)
This article discusses the importance of understanding the Psychology of Adolescent Development. Psychological interviews as a tool for understanding the identity, achievements and emotions of adolescents. Psychological interviews are a research method used to understand a person's behavior, emotions and thoughts. In the context of adolescents, psychological interviews can help understand the identity, achievements and emotions of adolescents by collecting information directly from research subjects. Here are some ways how psychological interviews can help understand these aspects: Identity: Psychological interviews can help understand how adolescents understand themselves and how they identify themselves in social contexts. In this way, researchers can understand how adolescents develop self-concept and how they interact with others. Achievement: Psychological interviews can help understand how adolescents experience the process of identity achievement and how they deal with identity crises. In this way, researchers can understand how teenagers develop courage and how they deal with changes in their lives. Emotional: Psychological interviews can help understand how teenagers experience emotions and how they control their emotions. In this way, researchers can understand how adolescents develop emotional abilities and how they interact with others in emotional contexts. In synthesis, psychological interviews can be used as an effective tool for understanding adolescent identity, achievement, and emotions. In this way, researchers can understand how adolescents develop self-concept, deal with identity crises, and control their emotions.